Effects of social popularity and time scarcity on online consumer behaviour regarding smart healthcare products: An eye-tracking approach. (January 2018) - Mou, Jian; Shin, Donghee
Abstract: Smart healthcare has become one of the most important issues for practitioners and researchers. In this study, we investigated the effects of social popularity and time scarcity on online consumer perceptions of smart healthcare products. To achieve this, we employed signaling theory and a laboratory-based eye-tracking design. We then collected both questionnaire and user visual fixation data for analysis. We found that social popularity is important with regard to consumers' trust, perceived product quality, and perceived value. Further, the questionnaire data showed that time scarcity is only important for perceived product quality and perceived value. We also found that time scarcity has a significant influence on online consumers' fixation attention. Moreover, interaction effects were found among the variables. Highlights: The effects of social popularity and time scarcity on online consumer perceptions of smart healthcare products. Signaling theory and conducted a laboratory-based eye-tracking design. Collected both questionnaire and user visual fixation data for analysis. Social popularity is important to consumers' trust, perceived product quality, and perceived value. Time scarcity is only important for perceived product quality and perceived value.